THE GROWTH OF MUSTARD USING HYDROPONICS AND AQUAPONICS SYSTEMS - Aulia Rakhman (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2015)
Hydroponics is an alternative way of farming in a limited area of urban.  It is Easy, controlled, and can be done on media without soil, even in a house.  In hydroponic watering system done  automatic and the environment can be controlled to prevent the plant from pests, it is suitable for people who spent more routine work in the office than at home. However, hydroponics nutrients is very difficult to obtain, even in Lampung no body has sold. Aquaponics is another alternative that could be used to grow crops in a limited area and the nutrients are easier to find because it uses fish waste. This study was conducted to evaluate whether the fish waste could replace hydroponic nutrients to support the growth of mustard plants.This research compared yield of mustard plants grown in three treatments, namely L1 (hydroponics), L2 (Aquaponics using comet fish), and L3 (Aquaponics using tilapia).  The study was conducted at the residence of Amin Khairi, St. Said Sabri, No. 58B, Kedaton, Bandar Lampung and Laboratory of Agricultural Engineering Department, University of Lampung.  The variables tested were plant height, leaf number, root length, and the total weight of harvest. The research showed that the growth of mustard plants at hydroponic was better than at aquaponics systems.  The average plant height at week four were 24,6 cm; 9,1 cm; 14,0 cm of L1, L2, and L3, respectively.  The average number of leaves at week four were 10,2; 7,2; 7,7 of L1, L2, and L3, respectively.  The average root lenght at week four were 27,3 cm; 10,6 cm; 15,0 cm of L1, L2, and L3, respectively. The total weight of mustard plants of L1, L2, and L3 were 77,08; 9,7; 28,6 grams; respectively.Keywords: hydroponics, Aquaponics, nutrients, mustard